ANALISIS FAKTOR PENENTU SIMPANAN MUDHARABAH BANK SYARIAH DI INDONESIA DAN MALAYSIA - Zulfa Nahdia Rahmi; Idah Zuhroh (Program Studi Ekonomi Pembangunan, 2020)
This research was conducted to find out how the development and influence of Islamic Bank Mudharabah Deposits in Indonesia and Malaysia. The analysis technique used is the panel with a purposive sampling, data regression with quantitative inferential type of the research is using secondary data from Financial Report data for each Sharia bank in Indonesia and Malaysia and World Bank data for 2010-2018. Simultaneous test results show that the value of F-count 192.775> F-table 2.56 of these values can be concluded that H0 is rejected, which means there is an influence simultaneously and together on the variable ROA, Profit Sharing, Inflation and GDP of the variable Mudharabah Deposits in Islamic banks in Indonesia in 2010-2018. Furthermore, for the Malaysian results, the F-count value is 49.99581> F-table 2.56 from that value that H0 is rejected, which means that there is a simultaneous and joint influence on the ROA, Profit Sharing, Inflation and GDP variables of the Mudharabah Deposit variable at the Bank Sharia in Malaysia in 2010-2018.